The Ethical Crisis in Law Enforcement Reflects the Failure of Modern Legal Philosophy to Balance Morality and Legality - Saputra, Muhammad Dewanto Adi (Media Hukum Indonesia (MHI), 2025)
This study examines the ethical crisis in law enforcement as a reflection of the failure of modern legal philosophy in balancing morality and legality. The disparity between moral norms and formal rules reveals how the Indonesian legal system experiences deviations, both normatively and in practice, leading to public distrust and the weakening of legal legitimacy. The dominance of positivism and focus on formal norms without moral scrutiny creates alienation between law and human values, exacerbating structural and organizational tensions in law enforcement agencies characterized by corruption, collusion, and low accountability. This collapse not only complicates the achievement of substantive justice but also hinders reforms responsive to social dynamics, thus demanding a reformulation of the legal philosophy paradigm capable of integrating moral values contextually and functionally. A critical approach to this modern paradigm affirms the need for harmonization between morality and legality as the primary foundation in building a just, meaningful, and sustainable legal system.